Ocean acidification along the Gulf Coast and East Coast of the USA. (15th April 2015) - Wanninkhof, Rik; Barbero, Leticia; Byrne, Robert; Cai, Wei-Jun; Huang, Wei-Jen; Zhang, Jia-Zhong; Baringer, Molly; Langdon, Chris
Abstract: As part of an effort to monitor changes in inorganic carbon chemistry of the coastal ocean, near-synoptic cruises are being conducted in the Northern Gulf of Mexico and along the East Coast of the United States. Here we describe observations obtained on a cruise in the summer of 2012 and compare them with results from a cruise following a similar track in 2007. The focus is on describing spatial patterns of aragonite saturation state ( Ω Ar ). This parameter is an indicator of ecosystem health, in particular for calcifying organisms. The results show large-scale regional trends from different source waters at the northeastern and southwestern edges of the domain, along with the modulating effects of remineralization/respiration and riverine inputs. The broader patterns and changes over five years along the coast can be well described by the impacts of large-scale circulation, notably changes in source water contributions. Changes in the well-buffered Loop Current and Gulf Stream with high Ω Ar impact the waters in the southern part of the study area. The less buffered southward coastal currents with low Ω Ar originating from the Labrador Sea and Gulf of St. Lawrence impact the Ω Ar patterns in the Northern regions. The expected 2% average decrease in Ω Ar in the surface mixed layer due to increasing atmospheric CO2 levels over the 5-year period is largely overshadowed by local and regional variability from changes in hydrography and mixed layer dynamics. Highlights: A summertime cruise provides the second comprehensive snapshot of ocean acidification. Aragonite saturation srtates are presented for the East and Gulf coasts. Northward decreases in saturation state are caused by decreases in inorganic carbon. Large-scale patterns and changes are dominated by ocean currents.